2016
DOI: 10.1002/14651858.cd011856.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of institutional smoking bans on reducing harms and secondhand smoke exposure

Abstract: We found evidence of an effect of settings-based smoking policies on reducing smoking rates in hospitals and universities. In prisons, reduced mortality rates and reduced exposure to secondhand smoke were reported. However, we rated the evidence base as low quality. We therefore need more robust studies assessing the evidence for smoking bans and policies in these important specialist settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 113 publications
0
51
1
Order By: Relevance
“…For example, there is a Chinese saying that “a cigarette builds a bridge, while wine builds a road” [38]. Cigarette sharing is a common social practice in China [14,39,40], and it may influence their openness to smoke inside recreational settings even if there is a smoking ban [8]. In addition to the three levels of factors discussed above, future studies should explore and address the barriers and facilitators related to social norms and culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, there is a Chinese saying that “a cigarette builds a bridge, while wine builds a road” [38]. Cigarette sharing is a common social practice in China [14,39,40], and it may influence their openness to smoke inside recreational settings even if there is a smoking ban [8]. In addition to the three levels of factors discussed above, future studies should explore and address the barriers and facilitators related to social norms and culture.…”
Section: Discussionmentioning
confidence: 99%
“…The main goals of a smoking ban in public places are to protect non-smokers from the dangers of environmental tobacco smoke and provide a supportive environment for those who want to quit smoking [6,7]. It has been well documented that smoking bans are beneficial for improving cardiovascular health outcomes and reducing smoking-related mortality [8]. Different countries have different attitudes towards the smoking bans and strategies for effective implementation.…”
Section: Introductionmentioning
confidence: 99%
“…There also have been tremendous increases both in understanding and addressing tobacco and its effects on child and adolescent health over the past 40 years. Both rates of prenatal tobacco and childhood SHS exposure (23)(24)(25)(26)(27) and rates of use have been identified and, in part, explicated and influences on initiation have been tracked (28,29) Multiple adverse child effects have been uncovered at the lowest levels of exposure (29)(30)(31)(32)(33) Effective practices, policies, and regulations have been discovered and implemented to greatly reduce cigarette use (34)(35)(36)(37), resulting in a profound decrease in exposure and initiation (38) Tobacco use and exposure to SHS are the leading preventable causes of morbidity and mortality in the United States and worldwide, killing more people than Tuberculosis, HIV, and Malaria combined (39,40). More than 1 billion tobacco-related deaths have taken place in this century (41), and virtually all adults start smoking before 18 years of age (28), with the mean age of initiation in the United States being 13 years (28).…”
Section: Children and Tobacco Exposure And Usementioning
confidence: 99%
“…Research on smoking bans in prisons has found some evidence that prisoners' second-hand smoke exposure decreases after partial smoking bans. Partial bans have also been shown to result in lower smoking related mortality, with some evidence that this is particularly the case for those with a diagnosed mental illness (6). Despite this, partial smoking bans in prisons have not been found to lead to a reduction in active smoking rates (6).…”
Section: Smoke-free Policies In Psychiatric Hospitals Might Reduce Stmentioning
confidence: 99%
“…Partial bans have also been shown to result in lower smoking related mortality, with some evidence that this is particularly the case for those with a diagnosed mental illness (6). Despite this, partial smoking bans in prisons have not been found to lead to a reduction in active smoking rates (6). The US Supreme Court has described prisoners' exposure to second-hand smoke as a 'cruel and unusual punishment' (7) and more research on smoking bans in prison populations is needed, as is research investigating the incidence of violence after the introduction of these policies.…”
Section: Smoke-free Policies In Psychiatric Hospitals Might Reduce Stmentioning
confidence: 99%